Staphylococcal Scalded Skin Syndrome in Neonate - K. Kouakou; M. E. Dainguy; K. Kassi (Case Reports in Dermatological Medicine)
We described a case of Staphylococcal Scalded Skin Syndrome in infant age of 21 days by discussing clinical and management issues. This newborn presented large erythematous, eroded, and oozing areas covered by epidermal skin flap. The average surface of cutaneous unsticking on admission was 31.35% of body surface area corresponding to lesions of superficial second-degree burns. An important biological inflammatory syndrome including positive C-reactive protein was found. Under treatment, erythroderma decreased within 7 to 10 days and the newborn was completely healed after 3 weeks of followup, with the disappearance of the inflammatory syndrome and total body surface restored. This clinical case report showed that SSSS remains a major dermatological problem in neonates. Therefore, its diagnosis should be made without doubt and its care should start earlier in a neonate emergency unit in order to have good prognosis. And the rigorous “search and destroy” policy based on screening of staff and patients and isolation of identified patients advocated in the United Kingdom should be applied in neonate units in Côte d’Ivoire.